The Performance of Sharia Insurance Companies based on Maqashid Sharia Index in Indonesia, Malaysia, and Bahrain: A Comparatif Study - Falikhatun Falikhatun; Dhanti Shofia (Universitas Muhammadiyah Malang, 2021)
This study aims to determine sharia Insurance companies performance according to the Maqashid Sharia index. The study was conducted using Simple Additive Weighting (SAW). The population and sample in this study are from Indonesia, Malaysia and Bahrain from 2016 to 2018. The analysis results show that Sharia Insurance in Indonesia, Malaysia and Bahrain have different performance ratio which is measured from the rank: 1) PT Asuransi Ramayana, Tbk (IDN), 2) AmMetLife Takaful Berhad (MYS), 3) Hannover Retakaful B.S.C (BHR), 4) PT Asuransi Ekspor Indonesia (IDN), 5) Takaful International Co.B.S.C (MYS), and 6) Etiqa Takaful Berhad (BHR). This study implies that the average performance ratio of Sharia Insurance in Indonesia is the best with 57.9%, followed by Bahrain with 29.8% and Malaysia with 27.2%. The results of this study are expected to have implications for the method of assessing the performance of Islamic insurance which does not only focus on financial performance, but also performance based on Maqashid Syariah. In addition, the results of this study are expected to enrich Islamic economics, particularly related to the measurement of sharia insurance performance.